Application of the Simple Multi Attribute Rating Technique in Scholarship Admission Decision Making at University - Purnomo Sidiq; yopi nugraha (RISTEC : Research in Information Systems and Technology, 2021)
The development of information systems and information technology brings a great influence and an extraordinary impact in making well-structured decisions. In its development, the decision support system provides real solutions to problems in managing scholarship receipts for students who are less economically capable but have excellent academic grades. With the management of scholarship receipts using the Simple Multi Attribute Rating Technique approach system by identifying the criteria for the highest score for the criteria for the cumulative assessment index, family income, number of dependents, academic achievement and organizational activities. So with the application of the Simple Multi Attribute Rating Technique, it produces a recommendation for scholarship acceptance. With the application of a decision support system using the SMART method, the recommendations generated by student data and information on student admissions will be more accurate